PENGARUH LAYANAN KONSELING KELOMPOK DENGAN TEKNIK RATIONAL EMOTIVE BEHAVIOR THERAPY ( REBT) TERHADAP FOMO (FEAR OF MISSING OUT ) PADA SISWA KELAS VIII B SMP NEGERI 17 KOTA BENGKULU: PENGARUH LAYANAN KONSELING KELOMPOK DENGAN TEKNIK RATIONAL EMOTIVE BEHAVIOR THERAPY ( REBT) TERHADAP FOMO (FEAR OF MISSING OUT ) PADA SISWA KELAS VIII B SMP NEGERI 17 KOTA BENGKULU - Elsa Oktitania Zahwa; Yessy Elita; Rita Sinthia (UNIVERSITAS BENGKULU, 2024)
This study aimed to describe the effect of group counseling services with rational emotive behavior therapy techniques on fear of missing out. The method used was an experiment with a one-group design, pre test-post test design. The population taken was 30 people in class VIII B. The sample in this study amounted to 6 students. The sampling procedure used purposive sampling. The data collection technique used a questionnaire with a Likert scale model. Data were analyzed using t-test (paired sample t-test). The t-test results show the value of t = 12.256 (p <0.05). The results of this study prove that group counseling services with rational emotive behavior therapy techniques can reduce the fear of missing out students in class VIII B at SMP Negeri 17 Bengkulu City. Keywords: fear of missing out, group counseling, rational emotive behavior therapy (rebt) techniques